Polyol-ester impact on boron foliar absorption and remobilization in cotton and coffee trees - Ciro Antonio Rosolem; Danilo Silva Almeida; Caio Vilela Cruz (Revista Brasileira de Ciência do Solo, 2020)
ABSTRACT Foliar fertilization can be recommended to treat boron (B) deficiency in coffee and cotton. Considering that B foliar fertilizers with polyol-boron complexes can affect B uptake and mobility differently within the plant, and coffee and cotton have different cuticles and stomata density, a differential response would be expected. We aimed to study the foliar application of boric acid combined with sorbitol on B uptake and translocation in cotton and coffee. Green-house grown plants received B as boric acid and a sorbitol-monoethanolamine complex and were sampled up to 96 h after application. Boron absorption was fast, reaching 60 and 80 % in cotton and coffee 96 h after application, respectively. Uptake rates and total B absorption were similar for the fertilizers. The proportion of B taken up by coffee is greater than by cotton likely because of the greater stomata density in coffee and less likely due to the higher amount of wax in cotton cuticle. Boron remobilization is higher in coffee as compared with cotton. Sorbitol seems to increase B transport in the transpiratory stream of cotton, but impairs remobilization in the phloem since B translocation to roots is decreased in both cotton and coffee.